2023
DOI: 10.3390/metabo13030337
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Lavenders from Section Stoechas: An Undervalued Source of Secondary Metabolites with Pharmacological Potential

Abstract: Globally, climate change and wildfires are disrupting natural ecosystems, thus setting several endemic species at risk. The genus Lavandula is widely present in the Mediterranean region and its species, namely, those included in the section Stoechas, are valuable resources of active compounds with several biological assets. Since ancient times lavenders have been used in traditional medicine and for domestic purposes. These species are melliferous, decorative, and essential oil-producing plants with a high eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 145 publications
2
7
0
Order By: Relevance
“…The remaining three articles used LP grown in Morocco [7,34] and Turkey [35]. The most abundant compounds found in all the LP extracts were the hydroxycinnamic acids (50%), which agrees with the literature available for LP [3,4] and other Lavandula species [6]. Nevertheless, previous studies from Lopes et al [3] identified only thirteen phenolic compounds, nine hydroxycinnamic acids and four flavonoids.…”
Section: Phenolic Compounds Profile and Quantificationsupporting
confidence: 75%
See 1 more Smart Citation
“…The remaining three articles used LP grown in Morocco [7,34] and Turkey [35]. The most abundant compounds found in all the LP extracts were the hydroxycinnamic acids (50%), which agrees with the literature available for LP [3,4] and other Lavandula species [6]. Nevertheless, previous studies from Lopes et al [3] identified only thirteen phenolic compounds, nine hydroxycinnamic acids and four flavonoids.…”
Section: Phenolic Compounds Profile and Quantificationsupporting
confidence: 75%
“…Phenolic compounds have been shown to positively affect human health, lowering the risk of diabetes, cancer, cardiovascular disease, and neurological problems [5]. Recent studies have shown that LP extracts have potential through their antioxidant, anti-inflammatory, antiproliferative, antimicrobial, anti-tyrosinase and anticholinesterase activity [6]. In addition, LP extracts have also shown an antihyperglycemic effect using in vitro, ex vivo and in vivo methods.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Domingues and Santos [ 61 ] in their comprehensive review have stated that M. pulegium EOs show significant chemical fluctuation, varying both in nature and number of constituents. This difference are potentially related to plant polymorphism [ 54 ], but can also be attributed to seasonal variation [ 62 ], and geographical origin [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that Lavender species have a significant quantity of total phenolic chemicals in hydroethanolic extracts, which L. stoechas having an exceptionally high phenolic content 50 . In the present study, the hydroethanolic extract from in vitro cultures of L. stoechas exhibited the highest concentration of phenolic compounds, with a value of 83.18 ± 3.07 mg GAE/g DW extract.…”
Section: Discussionmentioning
confidence: 99%